Effects of a quillaja saponaria extract on weanling pig growth performance and immune function during an acute enteric disease challenge - Turner, J.L.; Werner, J.R.; Hill, C.M.; Skjolaas, K.; Hogge, S.; Herkleman, K.; Minton, J. Ernest; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 96 pigs (initially 19 lb and 17 d of age) was used in a 28 d growth trial to determine the effects of Quillaja saponaria (QS) extract on weanling pig growth performance and immune function in response to enteric disease challenge with Salmonella typhimurium (ST). Experimental treatments were arranged in a 2 × 4 factorial with main effects of disease challenge (control vs. ST challenge) and dietary addition of QS (0, 4, 8, or 16 oz/ton). The results suggest little beneficial effect of QS on growth performance or immune response in the presence or absence of ST challenge.
Keywords: Swine; Weanling pigs; Disease challenge; Salmonella; Quillaja